Estrogen-sensitive activation of SGK1 induces M2 macrophages with anti-inflammatory properties and a Th2 response at the maternal-fetal interface - Yiyun Lou; Zhujing Fu; Ye Tian; Minhao Hu; Qijing Wang; Yuanyuan Zhou; Ning Wang; Qin Zhang; Fan Jin (BMC, 2023)
Abstract Background Decidual macrophages participate in immune regulation at the maternal-fetal interface. Abnormal M1/M2 polarization of decidual macrophages might predispose immune maladaptation in recurrent pregnancy loss (RPL). However, the mechanism of decidual macrophage polarization is unclear. We explored the role of Estradiol (E2)-sensitive serum-glucocorticoid regulated kinase (SGK) 1 in promoting macrophage polarization and suppressing inflammation at the maternal-fetal interface. Methods We assessed serum levels of E2 and progesterone during first trimester of pregnancy in women with or without threatened miscarriages (ended in live birth, n = 448; or early miscarriages, n = 68). For detection of SGK1 in decidual macrophages, we performed immunofluorescence labeling and western blot analysis applying decidual samples from RPL (n = 93) and early normal pregnancy (n = 66). Human monocytic THP-1 cells were differentiated into macrophages and treated with Toll-like receptor (TLR) 4 ligand lipopolysaccharide (LPS), E2, inhibitors or siRNA for in vitro analysis. Flow cytometry analysis were conducted to detect macrophages polarization. We also applied ovariectomized (OVX) mice with hormones exploring the mechanisms underlying the regulation of SGK1 activation by E2 in the decidual macrophages in vivo. Results SGK1 expression down regulation in the decidual macrophages of RPL was consistent with the lower concentration and slower increment of serum E2 from 4 to 12 weeks of gestation seen in these compromised pregnancies. LPS reduced SGK1 activities, but induced the pro-inflammatory M1 phenotype of THP-1 monocyte-derived macrophages and T helper (Th) 1 cytokines that favored pregnancy loss. E2 pretreatment promoted SGK1 activation in the decidual macrophages of OVX mice in vivo. E2 pretreatment amplified SGK1 activation in TLR4-stimulated THP-1 macrophages in vitro through the estrogen receptor beta (ERβ) and PI3K pathway. E2-sensitive activation of SGK1 increased M2 macrophages and Th2 immune responses, which were beneficial to successful pregnancy, by inducing ARG1 and IRF4 transcription, which are implicated in normal pregnancy. The experiments on OVX mice have shown that pharmacological inhibition of E2 promoted nuclear translocation of NF-κB in the decidual macrophages. Further more, pharmacological inhibition or knockdown of SGK1 in TLR4-stimulated THP-1 macrophages activated NF-κB by promoting its nuclear translocation, leading to increased secretion of pro-inflammatory cytokines involved in pregnancy loss. Conclusion Our findings highlighted the immunomodulatory roles of E2-activated SGK1 in Th2 immune responses by priming anti-inflammatory M2 macrophages at the maternal-fetal interface, resulting in a balanced immune microenvironment during pregnancy. Our results suggest new perspectives on future preventative strategies for RPL.